Efficient warm-white lighting using rare-earth-element-free fluorescent materials for saving energy, environment protection and human health. Issue 113 (25th November 2016) - Lin, Ching-Fuh; Tsai, Tsung-Yo; Chen, Kuan-Yu; Shen, Pin-Chun
Abstract : We explore an approach for efficient white light emission based on ZnSe:Mn nanoparticles without rare-earth and cadmium elements. This material opens up a new avenue for energy-saving, healthy, and environmentally benign lighting. Abstract : Solid-state white light emission is important for energy saving, but currently it is mainly based on environmentally unfriendly rare-earth doped phosphors or cadmium-containing quantum dots. Here, we explore an environmentally friendly approach for efficient white light emission based on ZnSe:Mn nanoparticles without rare-earth or cadmium elements. The emission is composed of a broad green-orange spectral band (525–650 nm) with the peak located at 578 nm and the color temperature is low, so it is particularly good for lighting at night to reduce risks to human health. Furthermore, the optimal absorption peak could be designed at 453 nm, which well matches the commercial blue-LED emission wavelength (445–470 nm). A quantum yield up to 84.5% could also be achieved. This rare-earth-element-free material opens up a new avenue for energy-saving, healthy, and environmentally benign lighting.